Exploring the Effects of an Ethical Climate on Integrity Development in Malaysia - Junus, Mariah Darus Mat (Dirasat: Human and Social Sciences, 2026)
Objective: The relationship between the ethical atmosphere and integrity among the officials of Universiti Utara Malaysia is explored in this paper. The growing amount of public complaints about government service delivery systems clearly shows integrity problems. Public complaints indicate the quality of the delivery service system, as they reflect the public’s dissatisfaction with government services. Public officials face the primary challenge of enhancing the consciousness of integrity, specifically among leaders. Previous studies reported that organisational systems and procedures compose ethical climate practices. Nevertheless, the connection between the ethical climate and integrity is inconsistent. Methods: This study used quantitative methodologies and distributed questionnaires to 50 respondents. Thirty respondents from fifty surveys made up the pilot research sample (average response rate: 52%). Results: The reliability analysis demonstrated that the ethical climate directly influences integrity. The correlation between ethical climate and integrity was 0.599 (p = 0.001 < 0.05). Thus, the hypothesis was supported. Conclusions: This study’s ethical climate centered on organisational members’ perception and acceptance of organisational policies and procedures. The results demonstrated that governmental policies and laws effectively established a favorable ethical environment that fostered the promotion of integrity among civil workers. The government significantly emphasizes fostering integrity within the public sector, as it is a fundamental basis for providing transparent and efficient services to the public. Therefore, this study concluded that the practice of integrity could be influenced by implementing an effective, ethical climate and gaining the acceptance of organisational members.